2016
DOI: 10.1016/j.juro.2016.04.081
|View full text |Cite
|
Sign up to set email alerts
|

Management of Renal Masses and Localized Renal Cancer: Systematic Review and Meta-Analysis

Abstract: Purpose-Several options exist for management of clinically localized renal masses suspicious for cancer, including active surveillance, thermal ablation and radical or partial nephrectomy. We summarize evidence on effectiveness and comparative effectiveness of these treatment approaches for patients with a renal mass suspicious for localized renal cell carcinoma. Materials and Methods-We searched MEDLINE®, Embase® and the Cochrane CentralRegister of Controlled Trials from January 1, 1997 through May 1, 2015. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
270
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(284 citation statements)
references
References 43 publications
9
270
0
5
Order By: Relevance
“…PCA preserves renal parenchyma and minimizes morbidity, convalescence time, and costs versus surgical excision 20,21 . Moreover, PCA offers similar cancer specific and metastasis free survival to the gold standard, partial nephrectomy 9 . Still, reported local treatment failure after PCA is higher than with surgical extirpation indicating that better patient selection or improved ablation techniques are needed.…”
Section: Resultsmentioning
confidence: 99%
“…PCA preserves renal parenchyma and minimizes morbidity, convalescence time, and costs versus surgical excision 20,21 . Moreover, PCA offers similar cancer specific and metastasis free survival to the gold standard, partial nephrectomy 9 . Still, reported local treatment failure after PCA is higher than with surgical extirpation indicating that better patient selection or improved ablation techniques are needed.…”
Section: Resultsmentioning
confidence: 99%
“…While local recurrencefree survival was worse for a single session of thermal ablation (HR 0.37, 95% CI 0.15-0.89), having repeat ablations levelled out the difference between this treatment modality and PN [70]. This is an important point to consider, as it reassures that retreatment with ablation or surgery is still a viable cancer control option after ablation-associated recurrence.…”
Section: Ablation Versus Surgerymentioning
confidence: 98%
“…A recent meta-analysis of 60 studies comparing treatment modalities in renal tumours with less than 7cm showed that cancer-specific and metastasis-free survival at 5 years were similar between PN and thermal ablation [70]. While local recurrencefree survival was worse for a single session of thermal ablation (HR 0.37, 95% CI 0.15-0.89), having repeat ablations levelled out the difference between this treatment modality and PN [70].…”
Section: Ablation Versus Surgerymentioning
confidence: 99%
“…There are several settings where ablation can be an option or recommended such as patients with high surgical risk, complex mass in a solitary kidney, prior partial nephrectomy, and multifocal, bilateral RCC or patient preference. 91,92 Patients who have undergone ablation therapy due to RCC should be followed with contrast-enhanced radiologic imaging (MRI or CT) to assess for residual enhancing disease and post procedure complication. The success of this procedure is CUAJ -CUA Guideline Kassouf et al Non-metastatic RCC followup defined by two types of imaging findings which are related to the zones of decreased perfusion, and the signal intensity (at MRI imaging), or attenuation (at CT).…”
Section: Followup After Ablationmentioning
confidence: 99%